Environmental Ethics: Catalyst for Human/ Nature Relationship in “A White Heron” - Chaulagain, Yashoda (Tribhuvan University Journal, 2020)
All the life forms have fundamental right to live in this universe. Human beings have duties, rights, and responsibilities towards the non-humans, and natural world. By not having a systematic and comprehensive account regarding the relationship between humans and the natural world, human beings are denying the importance of the life forms of other creatures in the world. Hence, the present research attempts to analyze the biocentric relationship of human beings with nature and its stewardship by being aware and knowledgeable of the world around them and protecting the world species. The study further argues the cooperative mechanism and symbiotic relationship between nature and human beings in this natural domain with reference to Jewett’s protagonist, Sylvia, who represents the symbol of mother earth by saving White Heron from the hunter. She restricts the Hunter to mastery over it. In addition, the work encompasses the conflict of nature with civilization by portraying the relationship of Sylvia, who preserves nature, from a foreigner, the Hunter who is concomitant with the danger of civilization. The Hunter who tracks the White Heron is from the city and hence stained by civilizations, sees nature is a place to exploit and desires the White Heron as another piece of his collection. In this sense, Sylvia represents herself true lover and preserver of the natural world and the Hunter is considered in complete opposition to the tranquility of the woodland.